Familial aggregation of arthritis-related diseases in seropositive and seronegative rheumatoid arthritis: a register-based case-control study in Sweden. Issue 1 (12th December 2014) - Frisell, Thomas; Hellgren, Karin; Alfredsson, Lars; Raychaudhuri, Soumya; Klareskog, Lars; Askling, Johan
Abstract : Objectives: Our objective was to estimate the risk of developing rheumatoid arthritis (RA) associated with a family history of non-RA arthritis-related diseases. This familial co-aggregation is of clinical interest since it is often encountered when assessing family history of RA specifically, but also informative on the genetic overlap between these diseases. Since anticitrullinated peptide antibodies/rheumatoid factor (RF)-positive and RF-negative RA have both specific and shared genetic factors, the familial co-aggregation was assessed separately for seropositive and seronegative disease. Methods: Nested case-control study in prospectively recorded Swedish total population data. The Multi-Generation Register identified first-degree relatives. RA and arthritis-related diseases were ascertained through the nationwide patient register. RA serology was based on International Classification of Diseases tenth revision coded diagnoses, mainly reflecting RF. Familial risks were calculated using conditional logistic regression. Results were replicated using the Swedish rheumatology register. Results: Familial co-aggregation was found between RA and every studied arthritis-related disease, but the magnitude varied widely, from juvenile idiopathic arthritis (JIA) (seropositive RA OR=3.98 (3.01 to 5.26); seronegative RA OR=5.70 (3.47 to 9.36)) to osteoarthritis (seropositive RA OR=1.03 (1.00 to 1.06); seronegative RA OR=1.05 (1.00 to 1.09)). The familial co-aggregation pattern of non-RA arthritis-related diseases was overall similar for seropositive and seronegative RA. Among those with family history of RA, relatives' other arthritis-related diseases conferred little or no additional risk. Conclusions: Although family history of several arthritis-related diseases may be useful to predict RA (eg, lupus and JIA), others (eg, osteoarthritis and arthralgia) are less useful. Seropositive and seronegative RA had rather similar familial co-aggregation patterns with arthritis-related diseases, suggesting that the two RA subsets are similar in the genetic factors that overlap with these diseases.